A gauge invariant Debye mass and the complex heavy-quark potential - Burnier, Yannis; Rothkopf, Alexander (Physics letters, 2016)
Following the original idea of Debye, we define and extract a gauge-invariant screening mass from the complex static in-medium heavy-quark potential VQQ¯, recently obtained from lattice QCD. To this end we derive a formula using concepts from both effective- and classical field theories that faithfully reproduces both the screened real- and the imaginary part of the lattice potential with a single temperature dependent fit parameter mD(T). Using values of the real part of VQQ¯ in a gluonic medium, we obtain Debye masses compatible with HTL perturbation theory.
Available online 14 December 2015
Gesehen am 24.04.2020